The future of power - Nye, Joseph S. (Public Affairs, 2011)
Power evolves. At the beginning of the twenty-first century, unsurpassed in military strength and ownership of world resources, the United States was indisputably the most powerful nation in the world. But the global information age is rendering these traditional markers of power obsolete. To remain at the pinnacle of world power, the United States must adopt a strategy that considers the impact of the internet on global power resources. The Future of Power examines what it means to be powerful in the twenty-first century and illuminates the road ahead.